COMPETITIVE POSITION AND PRODUCTIVE MODELIN PERU - Porlles Loarte, José (2005)
In the world competitiveness framework, the performance of Peru goes toward a worrying deterioration. Even more, when the construction of new forces to revert the process is not becoming visible, maintaininganeconomicmodeland, therefore, a productive model that does not guarantee the production and export of products with high aggregate value, to the extent that we continue depending on the natural resources. For purpose of analysis, the last reports of the World Economic Forum (WEF) on the competitiveness index and the evolution of the country, regional and world economy have been taken into consideration.